(untitled) (Journal of Engineering, 2024)
This paper describes the geotechnical properties of Al-Ammarah soil of Ammarah city in Messan Governorate-southern parts of Iraq. Data and other information taken from numbers of geotechnical reports that performed under the supervision of Consulting Engineering Bureau of Baghdad University. This research is devoted to study the correlation between different physical properties such as (LL, PI, LI, W., C.) with different mechanical properties such as (qu, Ces C SPT). The correlation is verified using simple regression analysis. From the regression results it was found that there is direct correlation between different parameters. By using the correlation-with some information- preliminary investigation stages and studies of any structure can be performed to find indicative design parameters